If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18/3=2x
We simplify the equation to the form, which is simple to understand
-18/3=2x
Simplifying:
-6=2x
We move all terms containing x to the left and all other terms to the right.
-2x=+6
We simplify left and right side of the equation.
-2x=+6
We divide both sides of the equation by -02 to get x.
x=-3
| (3y+5)(2y^2+5y-6)=0 | | 6x+16=34 | | -27n+14n+33-n=-23 | | -9/3=x | | X^2+1+2x=0 | | 8x+5-6x=11 | | 6x-5x^2-1=0 | | (2x)(3x^3)= | | x/3=-9 | | 9g^2-12g+4= | | 12x^2+35x+8=0 | | 9g^2-12+4= | | 4p^2+4p+1= | | 7x-3+8x=4x+4-6x | | X^2+5+1=0 | | 5y=7x-1 | | 2(3x^2+14x-5)= | | 2(3x^2+14-5)= | | 6x^2+28-10= | | 6x^2-5=0 | | 6d-45=45 | | 8x-3x^2=4 | | 7x+2=6x+9 | | (2x+3)(x-2)=(X+1)(x-6) | | 4k^2+12k+9= | | 8x-8= | | (3x-8)(2x+1)= | | 2x-5=3x/2 | | 6d^2-96= | | 2x=295 | | 5(4x+3)+2(x+6)=3(x+8) | | 7x=4x-13 |